Education and the racial dynamics of settler colonialism in early America - Spady, James O'Neil, 1968- author.
1 online resource.
Keywords: "This is the first historical monograph to demonstrate settler colonialism's significance for Early America. Based on a nuanced reading of the archive and using a comparative approach, the book treats settler colonialism as a process rather than a coherent ideology. Spady shows that learning was a central site of colonial struggle in the South, in which Native Americans, Africans, and European settlers acquired and exploited each other's knowledge and practices. Learned skills, attitudes, and ideas shaped the economy and culture of the region and produced challenges to colonial authority. Factions of enslaved people and of Native American communities devised new survival and resistance strategies. Their successful learning challenged settler projects and desires, and white settlers gradually responded. Three developments arose as a pattern of racialization: settlers tried to prohibit literacy for the enslaved, remove indigenous communities, and initiate some of North America's earliest schools for poorer whites. Fully instituted by the end of the 1820s, settler colonization's racialization of learning in the South endured beyond the Civil War and Reconstruction"--